Systematic search for post period-minimum cataclysmic variables: A short review - Vitaly V. Neustroev; Christian Knigge; Sergey V. Zharikov (Italy, 2022)
Standard evolutionary theory suggests that cataclysmic variables (CVs) evolve from longer to shorter orbital periods. CVs that have passed beyond the period minimum and are evolving back towards longer periods are called the period bouncers. CVs of the WZ Sge-type have been long considered as potential period-bounce candidates. However, only very few of recently discovered WZ Sge-type stars were observed spectroscopically in quiescence due to their faintness. The lack of information on many of WZ Sge-type stars does not allow us to put restrictions on their system parameters and to confirm or deny their period bounce nature. Here we present a novel, simpler yet equally valuable approach based on multicolour broadband photometry to reveal the best period bounce candidates. By adopting such an approach, we performed a pilot study of a sample of WZ Sge-type stars and accreting WDs and have found solid evidence for very low luminosity donor stars in several of them.
2017 Golden Age of Cataclysmic Variables and Related Objects IV, GOLDEN 2017